KEBIJAKAN PENGEMBANGAN PASOKAN PANGAN DOMESTIK TELUR AYAM DI KABUPATEN PATI - Suroso, Suroso (Jurnal Litbang: Media Informasi Penelitian, Pengembangan dan IPTEK, 2018)
ENGLISHFood supply is very important to ensure adequate food comsumption for community. The objectives of the research are: (1) to analyze the production of chicken eggs; (2) to analyze the consumption of chicken eggs; and (3) to analyze the balance and food supply chain of chicken eggs in the study area.This research used descriptive-quantitative approach. The research used primary and secondary data. Data collecting was conducted by interview and survey. The reserch used descriptive analysis. The research has 3 findings. Firstly, in Pati Regency production of race chicken eggs are 13,008,982 granules equal to 455,922.69 kilograms and the consumption of race chicken eggs are 455,922.69 kilograms so it has minus balance (-7,465,713.83) kilograms of race chicken eggs for a year. Secondly, the production local chicken eggs are 23,355,221 granules eggs equal to 830,745.21 kilograms and the consumption of local chicken eggs are 198,392.25 kilograms so it has surplus balance 632,353 kilograms of local chicken eggs for a year. Thirdly, in composite, the production of chicken eggs is less than consumption of chichen eggs and the supply of chicken eggs in Pati Regency is mostly derived from other regions including: Tuban, Blitar, Lamongan, Nganjuk and Bojonegoro. Then the sale trade of chicken eggs fot outside market is just little especially in the market of Kudus Regency. INDONESIAPasokan pangan sangat penting untuk menjamin konsumsi pangan memadai bagi masyarakat. Penelitian ini memiliki tujuan: (1) menganalisa tingkat produksi telur ayam; (2) menganalisa tingkat konsumsi telur ayam dan (3) menganalisa neraca dan rantai pasokan pangan komoditas telur ayam di area studi. Penelitian ini menggunakan pendekatan deskriptif-kuantitatif. Data penelitian meliputi data primer dan data sekunder. Pengumpulan data primer dilakukan dengan menggunakan teknik wawancara dan survey. Penelitian ini menggunakan analisis deskriptif. Penelitian ini memiliki 3 temuan. Pertama, Kabupaten Pati memiliki produksi telur ayam ras sebanyak 13.008.982 butir setara dengan 455.922,69 kg dan konsumsi telur ayam ras sebanyak 8.116.162,95 kg maka daerah ini memiliki neraca minus (-7.465.713,83) kg telur ayam ras per tahun. Kedua, Kabupaten Pati memiliki produksi neto telur ayam buras 23.355.221 butir setara dengan 830.745,21 kg dan konsumsi telur ayam buras sebanyak 198.392,25 kg maka daerah ini memiliki neraca surplus 632.353 kg telur ayam buras per tahun. Ketiga, secara komposit, produksi telur di Kabupaten Pati lebih sedikit dibandingkan konsumsi telur dan rantai pasokan pangan komoditas telur ayam sebagian besar didatangkan dari luar daerah meliputi: Tuban, Blitar, Lamongan, Nganjuk dan Bojonegoro. Kemudian perdagangan penjualan telur ayam keluar daerah relatif kecil dengan target pasar Kabupaten Kudus.